Urban legends: Turkish kayık ‘boat’ and “Eskimo” qayaq ‘kayak’ - de la Fuente, José Andrés Alonso (Studia Linguistica Universitatis Iagellonicae Cracoviensis, 2015)
The main goal of this paper is to show that the proposed relationship between Turkish kayık ‘boat’ and Eskimo qayaq ‘kayak’ is far-fetched. After a philological analysis of the available materials, it will be proven that the oldest attestation and recoverable stages of these words are kay-guk (11th c.) < Proto-Turkic */kad-/ in */kad-ï/ ‘fir tree’ and */qan-yaq/ (see Greenlandic pl. form kainet, from 18th c.) < Proto-Eskimo */qan(ə)-/ ‘to go/come (near)’ respectively. The explicitness of the linguistic evidence enables us to avoid the complex historical and cultural (archaeological) observations related to the hypothetical scenarios concerning encounters between the Turkic and Eskimo(-Aleut) populations, so typical in a discussion of this issue. In the process of this main elucidation, two marginal questions will be addressed too: the limited occasions on which “Eskimo” materials are dealt with in English (or other language) sources, and the etymology of (Atkan) Aleut iqya- ‘single-hatch baidara’.